Bounds for Viscoelastic Properties of Heavy-oil Rocks - Makarynska, D.; Gurevich, Boris (EAGE, 2010)
Heavy oils exhibit viscoelastic behaviour which is strongly frequency- and temperature- dependent. Due to the viscoelastic rheology of heavy oils the common elastic bounding methods such as Hashin-Shtrikman bounds are not rigorous for heavy-oil rocks. In this paper, we demonstrate that viscoelastic bounds of Milton and Berryman for the effective shear modulus of a two phase three-dimensional isotropic composite can be used as rigorous bounds for heavy-oil rocks. The viscoelastic bounds provide an effective tool for testing laboratory measurements and theoretical predictions for heavy-oil rocks.